Expecting too much, foreseeing too little? Behavioral explanations for the sell low-buy high puzzle in smallholder market participation - De Weerdt, Joachim; Dillon, Brian; Hami, Emmanuel; Van Campenhout, Bjorn; Nabwire, Leocardia (International Food Policy Research Institute, 2024)
It is often observed that smallholder farmers sell most of their marketable surplus immediately after the harvest when seasonal price movements reach their lowest point, instead of waiting just a few more months until prices recover. Most explanations for this seemingly sub-optimal behavior focus on economic or infrastructural issues, such as credit constraints or lack of storage facilities. In this study, we take a closer look at two potential behavioral explanations. One explanation focuses on household expenditure and assumes that households face challenges in accurately predicting future expenditures, systematically underestimating future needs. A second potential explanation focuses on household income, where motivated reasoning leads farmers to sell too early and/or at low prices. To test these hypotheses, we conduct two planning-based interventions among a sample of Malawian smallholder farmers: (1) a detailed expense budget and (2) a sales plan with explicit commitment to timing of sales, quantities and prices. The treatments were administered at harvest time in May 2022 and April 2023.